2011
DOI: 10.1891/0889-8391.25.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior and Alcohol Consumption in Individuals With Panic Attacks

Abstract: Individuals with anxiety often report greater smoking and drinking behaviors relative to those without a history of anxiety. In particular, smoking and alcohol use have been directly implicated among individuals experiencing panic attacks, diagnosed with panic disorder, or high on panic-relevant risk factors such as anxiety sensitivity. Less is known, however, about specific features of panic that may differentiate among those who do or do not use cigarettes or alcohol. The purpose of the current study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
10
0
8
Order By: Relevance
“…In addition to panic attacks being a relatively common phenomenon (3), empirical evidence suggests that panic attacks co-occur with smoking at rates that exceed those found in the general non-psychiatric population (7-9). In the National Comorbidity Survey, current smoking rates among adults with a history of panic attacks were significantly greater than those reported among respondents with no mental illness and quit rates were significantly lower (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to panic attacks being a relatively common phenomenon (3), empirical evidence suggests that panic attacks co-occur with smoking at rates that exceed those found in the general non-psychiatric population (7-9). In the National Comorbidity Survey, current smoking rates among adults with a history of panic attacks were significantly greater than those reported among respondents with no mental illness and quit rates were significantly lower (10).…”
Section: Introductionmentioning
confidence: 99%
“…In line with theoretical models of anxiety and smoking comorbidity (17), it was hypothesized that a history of panic attacks may impact smoking by first increased negative affect followed by increased negative reinforcement-based smoking motivation; that is, the indirect effects of the proposed mechanisms (negative affect and smoking motives) are theorized to sequential impact smoking processes. These effects were expected to be evident above and beyond the variance accounted for by gender, age, marital status, alcohol and cannabis use, depressive symptomology and tobaccorelated medical problems; factors often related to both smoking and panic attacks (9,17,26). …”
Section: Introductionmentioning
confidence: 99%
“…Pētījumi par panikas simptomu saistību ar alkohola un citu atkarību izraisošo vielu lietošanu nav snieguši vienprātīgus secinājumus. Pieaugušo grupās ir pētījumi, kas norāda uz panikas simptomu saistību ar tabakas smēķēšanu (Mathew et al, 2011), citi šādu saistību neatklāj (Valentiner et al, 2004). Arī alkohola lietošanas saistība ar panikas simptomiem un traucējumiem nav viennozīmīga -ir pētījumi, kas neatklāj sakarības (Valentiner et al, 2004), un pētījumi, kas norāda uz ciešām sakarībām (Zimmer man et al, 2003;Mathew et al, 2011).…”
Section: Panikas Simptomu Saistība Ar Alkohola Un Citu Atkarību Izraiunclassified
“…In research with adult (e.g., Mathew et al, 2011) and adolescent (e.g., Zimmerman et al, 2003) samples, a positive relation between alcohol use and panic-spectrum problems has been observed. Indeed, with only two exceptions (i.e., Clark et al, 1995; Hayward et al, 1995), a high degree of co-occurrence has been identified in adolescent samples across qualitative (Gardner & Kutcher, 1993), laboratory-based (Blumenthal et al, 2012), and prospective designs (e.g., Goodwin et al, 2004).…”
mentioning
confidence: 97%